Conference on Coherence and Quantum Optics 2007
DOI: 10.1364/cqo.2007.jwc68
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Photon Server with Just One Atom

Abstract: Neutral atoms are ideal objects for the deterministic processing of quantum information. Entanglement operations have been performed by photon exchange [1] or controlled collisions.[2] Atom-photon interfaces were realized with single atoms in free space [3,4] or strongly coupled to an optical cavity. [5,6] A long standing challenge with neutral atoms, however, is to overcome the limited observation time. Without exception, quantum effects appeared only after ensemble averaging. Here we report on a single-photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 1 publication
1
36
0
Order By: Relevance
“…It is worth to mention that obtained result which is typical for plasmonic structures, corresponds well with quality factor value calculated according to equations (8)(9)(10).…”
supporting
confidence: 85%
“…It is worth to mention that obtained result which is typical for plasmonic structures, corresponds well with quality factor value calculated according to equations (8)(9)(10).…”
supporting
confidence: 85%
“…It is confirmed that the electron spin relaxation time and the dephasing time of NV centers can be milliseconds at room temperature in recent researches 22 33 34 . On the other hand, recent experimental technology can generate 300000 high quality single photons within 30 seconds 36 , which ensures our schemes can be accomplished within the valid duration. Moreover, the current equipment technology of optical resonator can make the mode leak rate κ s negligible compared to the decay rate in output mode κ .…”
Section: Discussionmentioning
confidence: 99%
“…At present, several types of quantum systems capable of serving as truly deterministic single-photon sources have been investigated 7 (see Fig. 1), including trapped atoms 8 and ions, 9 single molecules, 10 quantum dots, 11 color centers, 12 atomic ensembles, 13 and mesoscopic quantum wells. 14 The solid state sources such as quantum dots and lattice defects are naturally interesting for future commercial quantum devices.…”
Section: Available Single-photon Sourcesmentioning
confidence: 99%